Drought resistance and resilience: The role of soil moisture–plant interactions and legacies in a dryland ecosystem - Hoover, David L.; Pfennigwerth, Alix A.; Duniway, Michael C. (The Journal of ecology, 2021)
In many regions of the world, climate change is projected to reduce water availability through changes in the hydrological cycle, including more frequent and intense droughts, as well as seasonal shifts in precipitation. In water‐limited ecosystems, such as drylands, lower soil water availability may exceed the adaptive capacity of many organisms, leading to cascading ecological effects during (concurrent effects) and after drought (legacy effects). The magnitude and duration of concurrent and legacy effects depends on drought intensity, duration and timing as well as the resistance and resilience of the ecosystem. Here, we investigated the effects of drought seasonality and plant community composition on two dominant perennial grasses, Achnatherum hymenoides (C3 photosynthesis) and Pleuraphis jamesii (C4 photosynthesis), in a dryland ecosystem. The experiment consisted of three precipitation treatments: control (ambient precipitation), cool‐season drought (−66% ambient precipitation November–April) and warm‐season drought (−66% ambient precipitation May–October), applied in two plant communities (perennial grasses with or without a large shrub, Ephedra viridis) over a 3‐year period. We examined the concurrent and legacy effects of seasonal drought on soil moisture, phenology and biomass. Drought treatments had strong concurrent and legacy effects on soil moisture, which impacted the phenology and biomass of the two grasses. Drought reduced growing season length by delaying green‐up (cool‐season drought) or advancing senescence (warm‐season drought) and reduced biomass for both species. Biomass and phenology legacy effects from drought emerged in the second and third years of the experiment. While we observed differential sensitivity to drought legacies between the two grasses, we found limited evidence that shrub presence had interactive effects with the drought treatment. Synthesis. The results from this study highlight how abiotic and biotic legacies can develop and influence a community's resistance and resilience to subsequent droughts. When the frequency of repeated extreme events, such as recurring seasonal droughts, exceeds the capacity of organisms or ecosystems to recover (i.e. resilience), persistent drought legacies can reduce the resistance to subsequent drought events. Overall, these results highlight how drought legacies are a product of ecological resistance and resilience to past drought and can influence ecosystem vulnerability to future droughts. The results from this study highlight how abiotic and biotic legacies can develop and influence a community's resistance and resilience to subsequent droughts. When the frequency of repeated extreme events, such as recurring seasonal droughts, exceeds the capacity of organisms or ecosystems to recover (i.e. resilience), persistent drought legacies can reduce the resistance to subsequent drought events. Overall, these results highlight how drought legacies are a product of ecological resistance and resilience to past drought and can influence ecosystem vulnerability to future droughts.